Analisis Kesulitan Siswa Dalam Memahami Materi IPA dan Upaya Mengatasinya Pada Kelas V di MI Islamiyah Bogor - Ahmad Syarif; Miftahul Janah; Asep Nuhdi (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2023)
This study aims to analyze students’ difficulties in understanding science material and efforts to overcome them in clas V at MI Islamiyah State School in the 2021/2022 academic year. The method used in this research is case study with research data sources are observations conducted directly to student. In qualitative research, the researcher acts as an instrument and usescollection techniques and participant observation and interviews. The results showed that science learning at MI Islamiyah was less effective. There are severeal factors that cause students to have difficulty understanding science material at school, including: lazy students, lack of motivation from teachers, not focusing on learning, lack of attention from both parents, lack of enthusiasm in learning, family problems, physical disorders, and interest in reading. Drop from the results of this study the total number of students in class V amounted to 34 while there wewe 6 students who had difficulty in learning science material at MI Isalmiyah. The teacher’s efforts to overcome students who have learning difficulties in class are: the teacher always encourages students to continue to actively learsduring class lessons, the teacher must always remember that students have different character traits from each other, the teacher gives clear directions to students, the teacher must give words of motivation to students and the teacher always gives praise to every student, especially students who are having difficulty understanding science material at school so that learning activities run well. Keywords : Learning difficulties science, how to overcome